Report from the interdisciplinary conference on the future of civics and social science education in the Czech Republic: "Citizen" in times of crisis - Stanek, Antonin (Civilia, 2025)
The Platform of Departments for Civic Education held the first interdisciplinary conference dedicated to the future of civic education and social science education in the Czech Republic on September 16-18, 2024 at the University Center Telc, which is a workplace of Masaryk University.